Physiologic simulator to predict the arterial oxygen saturation at extreme heights - Reyes Lazalde, Arturo; Pérez-Bonilla, M. E.; Fuchs-Gómez, O. L.; Reyes-monreal, M. (Revista Mexicana de Ingenieria Biomedica, 2011)
A simulator («Alturas») was developed to calculate the levels of arterial oxygen saturation (SaO2) at heights ranging from small to extreme. The results of the simulations were compared to published experimental data in order to validate the accuracy of the simulator. Three types of cases were used in the comparison: (1) non acclimatized people at heights ranging from 20 m to 4,162 m above sea level, (2) inhabitants of mountain zones living at heights between 1,692 m and 4,230 m, (3) people in ascension of a mountain at heights from 4,250 m to 7,500 m. The statistical analysis shows no significant difference between the reported clinical values and the values generated by the simulator. The simulator is able to predict the different average values of SaO2 at different heights under three conditions: recently arrived, in adaptation and in acclimatization.